Identifying and overcoming the risk of fraud in the Malaysian electronic land administration - Abdul Karim, Nor Shariza; Raja Othman, Raja Zarina; Ismail, Mohd Shukri; Maidin, Ainul Jaria (2011)
This paper attempts to provide a brief research report in risk management and security areas pertaining to threats due fraud in the Malaysian Electronic land administration system. Analyses of potential threats are provided based on evidences from various past researches and working papers, documentations, and field visits. Based on the findings, the researchers classified and described fraud existence, and suggested means of which such threats can be reduced through appropriate use of technology, policies, and strategies.